If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 8z = 42 Solving 2x + 8z = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8z' to each side of the equation. 2x + 8z + -8z = 42 + -8z Combine like terms: 8z + -8z = 0 2x + 0 = 42 + -8z 2x = 42 + -8z Divide each side by '2'. x = 21 + -4z Simplifying x = 21 + -4z
| 3x+3x+7+6=37 | | -7w+20.7=3.2 | | -9w-5+6w=16 | | 6/7-15/28 | | 5x+11=-7x-16 | | 36-10x=5x+22 | | 1/3-2/9-1/3 | | 2x-6=8x+4-3x | | 21/3x-24 | | 3+3-(x-2)=3x+4 | | f(6)=6-3/4(6)-3 | | 2(x+5)=2(x+9) | | 8x-15x-30x-51x=53+31x-17 | | 5xv=20 | | 90/10x-40 | | n-17=13+7n | | 97-9x=2x+3 | | N^3+12n^2+48n-64=0 | | 3x+20=8x+25 | | 2x+3=97-9x | | -4-9b=8u | | 5x=3-7x | | 2(3X+1)=X+2 | | x^3+7x^2+16x+112=0 | | 4x-3(2x+8)=-36 | | 2/3(x=7)=10 | | 101-5x=126-10x | | e=f+x | | 0.7(3s+4)-1.1s=7.9 | | K/-3=4 | | 5x+4y=48 | | (1-lnx)/(x^2)=0 |